2020
DOI: 10.21203/rs.3.rs-22924/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using volunteered geographic information to assess mobility in the COVID-19 pandemic context: cross-city time series analysis of 41 cities in 22 countries from March 2nd to 26th 2020

Abstract: Background: Restricting mobility is a central aim for lowering contact rates and preventing COVID-19 transmission. Yet the impact on mobility of different policies of restriction is not well-understood.Methods: Trends were evaluated using Citymapper’s mobility index covering 41 cities worldwide between 2nd and 26th March 2020, expressed as percentages of typical usage periods from 0% as the lowest and 100% as normal. China and India were not covered. Multivariate fixed effects models were used to estimate the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Recent studies suggested that mobility in the general public reduced with increase in stringency. 17 School closure was found to be associated particularly with time staying at home. While youths who self-harm may avoid presentations at hospitals out of fear of contracting and spreading the disease or concerns of being labelled as an ‘attention-seeker’, 11 stringent government restrictions might have inadvertently further discouraged help-seeking behaviour in those who were in need.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies suggested that mobility in the general public reduced with increase in stringency. 17 School closure was found to be associated particularly with time staying at home. While youths who self-harm may avoid presentations at hospitals out of fear of contracting and spreading the disease or concerns of being labelled as an ‘attention-seeker’, 11 stringent government restrictions might have inadvertently further discouraged help-seeking behaviour in those who were in need.…”
Section: Discussionmentioning
confidence: 97%
“…Studies across the globe have suggested that stringency effectively reduced mobility in the community. 17 Referrals to child and adolescent mental health services displayed various patterns in different periods of the lockdown. 18 It is possible that the unintended consequences of lockdown varied with the magnitude of lockdown stringency, creating barriers to emergency presentations.…”
mentioning
confidence: 99%